Association between Gross Motor Competence and Physical Fitness in Chilean Children Aged 4 to 6 Years - Andrés Godoy-Cumillaf; Paola Fuentes-Merino; Frano Giakoni-Ramírez; Daniel Duclos-Bastías; José Bruneau-Chávez; Diego Vergara-Ampuero; Eugenio Merellano-Navarro (MDPI AG, 2024)
The preschool period is considered critical for the development of motor competence, but as far as we know, no studies have investigated the association between motor competence and physical fitness in Chilean children. The aim of this study was to analyse the association between gross motor competence and physical fitness, controlling for possible confounding factors. A cross-sectional study was conducted with a sample of 144 preschool children (56.25% girls) with an average age of 5.3 years (4 to 6 years) from the Araucanía region, Chile. Motor competence was measured using the Children's Movement Assessment Battery, 2nd Edition (MABC-2). Regarding physical fitness, the components of cardiorespiratory fitness, lower body muscle strength and speed/agility were evaluated using the Battery to Assess FITness in PREschool (PREFIT). Partial correlation models and analysis of variance (ANCOVA) were used to assess differences in physical fitness between motor competence categories, controlling for age and body mass index. The mean fitness scores for cardiorespiratory fitness, lower body muscle strength and speed/agility components were significantly higher in children with higher gross motor competence. In terms of effect size, large values were found for the lower body strength component in model 1 for boys and in model 2 for the total samples of girls and boys. The results of this study suggest that good levels of gross motor competence are associated with better physical fitness levels.